Physiological and transcriptomic analyses reveal critical immune responses to hypoxia and sulfide in the haemolymph of clam Tegillarca granosa - Yang, Zhengkuan; Wang, Yihang; Jiang, Puyuan; Xia, Feiyu; Xu, Ying; Tian, Xiaofei; Zhang, Xiumei (Frontiers in Marine Science, 2023)
Hypoxia and sulfide are inducing potential damage to aquatic organisms. However, the effects of hypoxia and sulfide on their immune systems and molecular mechanisms are not fully understood. In the present study, the clam Tegillarca granosa was exposed to hypoxia alone or in combination with sulfide (0.1, 0.5 mM) to investigate the physiological and transcriptomic responses in haemolymph. The IBR analysis revealed that moderate sulfide stimulated immune responses via increasing the total hemocyte counts, phagocytic activity, antibacterial activity, and antioxidant activity. The transcriptomic analysis revealed many critical signaling pathways (Toll and Imd, FoxO, NLR) and biological processes (antimicrobial/antibacterial peptide, interferon, interleukin, leukocyte, lymphocyte, mitophagy) involved in the immunostimulation. Our results would offer insights into the sulfide-tolerant molecular mechanisms in this species and provide a useful tool for assessing the integrated biological impacts of hypoxia and sulfide on shellfish.